PHOTOGRAPHY IN THE ARCHIVES: STUDY ON THEORETICAL APPROACHES TO ARCHIVAL PROCESSING - Machado, Bruno Henrique; Madio, Telma Campanha de Carvalho [UNESP] (FapUNIFESP (SciELO), 2024)
Institutional photography, like any other record, should follow formal rules and institutionalized technical procedures for its production as an archival record. In this sense, the present text aims to present, in a theoretical way, the approaches given to photographs, whether analog or digital, in institutional environment; besides tangenting some guidelines for the archival maintenance of these documents. Thus, we analyzed some proposed projects that seek to maintain institutional photographs as archival records, namely: the international project International Research on Permanent Authentic Records in Electronic Systems (InterPARES), and the national project on resolutions and recommendations of the Technical Chamber of Audiovisual, Iconographic, Sound and Musical Documents (CTDAISM) and National Archive of Brazil. As a result, it was possible to identify, in the recommendations, that there is a consensus about the concerns of maintaining these institutional photographs, as guided by Archival Science. In this way, we conclude that it will only be possible to attribute a sense of archival record to photographs in institutions that are fully engaged in document management, promoting the maintenance of existing links with the contexts of production, circulation and use.
FOTOGRAFIA NOS ARQUIVOS: ESTUDO SOBRE AS ABORDAGENS TEÓRICAS PARA TRATAMENTO ARQUIVÍSTICO
Keywords: Archival record; Archival science; Photography; Records management